Coping Strategies of Family Caregiver in the Treatment of Mental Disorders - Hastuti, Fitriana Dwi; Sulandari, Santi (Universitas Muhammadiyah Surakarta, 2019)
Purpose: People with mental disorders cause interference with the function of interaction and inability to take care of themselves so that they need someone (caregiver). The caregiver has a vulnerability to stress because it has to meet the needs of people with mental disorders. The purpose of this study is to describe the coping strategies used by caregivers in caring for people with mental disorders. Methods: The approach used in this research is qualitative with a case study research design. This research involved four people (main informants & supporting informants). The main informant criteria are living in one house with a mental disorder, helping to meet the needs of sufferers and the status of the informant as a family. The sampling technique chosen was purposeful sampling. Analysis of the data used is content analysis. Results: This study indicate that caregiver problems include low knowledge, economy, and community reaction while coping used by caregiver is intended to solve the problems faced so that the knowledge possessed by caregiver affects the coping used such as how to treat, choose treatment, trust in heirlooms until the reaction in solving problems that involve the community. Besides, the relatively low economic level influences the use of coping, such as denial, considering the effectiveness & seeking social support.Value: Caregiver burden is the strongest predictor that can cause family conflict so that the need for interventions in the form of support and psychoeducation is carried out regularly.